A lost portrait by Pieter Cristus and its contemporary Italian copy an exploration of Flemish-Italian artistic interactions in the fifteenth century - Verheyen, Jan (2024)
In 2016, a captivating fifteenth-century portrait of a self-assured man, dressed entirely in accordance with the Burgundian-Flemish fashion, featuring a striking black headdress, caught the attention of experts engaged by the Swiss auction house Koller. Despite the attached thin oak slats above and below, it was evident that the panel was painted on Mediterranean pine wood. Since then, the panel has undergone numerous technical examinations, both in Italy and Belgium. This contribution presents the results of complementary technical and art historical analyses, gradually forming a clear picture of a complex fifteenth-century reality. The panel emerges as a unique witness to a cosmopolitan Eyckian-inspired Flemish painter, a fashion-conscious Italian businessman travelling between Bruges and Lucca, and a talented Italian painter who adeptly imbues a Tuscan panel with Burgundian allure. While the identities of the painter and the sitter may remain anonymous, the significance of this gem is profound: the transcendent, cross-border, unifying visual language of late medieval Europe, poised with confidence on the cusp of modernity, crystallizes in the blue sky, black velvet, and subtly illuminated facial tones of this "Burgundian Portrait".